PENYELESAIAN SENGKETA MASYARAKAT MELALUI PERADILAN ADAT DI DESA TAMPUR PALOH - Ary Raihan; Filkarwin Zuska (Aceh Anthropological Journal, 2022)
This study aims to analyze the apparatus of customary justice and the code of ethics in dispute resolution and how the dispute resolution model is used in the Gampong customary court. For some cases, a husband and a wife who are divorced in customary court are officially divorced according to customary law, but they do not have formal legality so other stages are needed to obtain formal legality. The result of this study showed that the dispute court in the Gayo community, Tampur village Simpang Jernih, East Aceh, for the judicial disputes that occurred in the Tampur Paloh community still broadly used the customary Acehnese traditional court, even though the dispute occurred with a different ethnic group.  The statement above was confirmed by the traditional figure of Tampur Paloh which was considered the most senior at the time. There were two stages for the implementation of the customary judicial apparatus; the first stage was through the Gampong traditional institution and the second through the traditional institution at the settlement level. From receiving reports and evaluating conflicts to the final trial stage and issuing decisions in customary court, customary administrators were responsible for all stages of customary law courts. Customary court decisions had also to do justice for both parties, according to customary court officials.Abstrak: Penelitian ini bertujuan untuk menganalisis perangkat peradilan adat dan kode etik dalam penyelesaian sengeta serta bagaima model penyelesaian sengketa yang digunakan dalam peradilan adat gampong. Beberapa kasus misalnya suami istri yang bercerai di pengadilan adat secara resmi bercerai menurut hukum adat, tetapi karena tidak mempunyai kekuatan hukum formal, masih diperlukan tahapan lain untuk memperoleh legalitas formal. Dari hasil penelitian ini menunjukan bahwa peradilan sengketa dalam masyarakat gayo Desa Tampur Paloh Simpang Jernih, Aceh Timur, untuk peradilan sengketa yang terjadi dalam masyarakat Tampur Paloh secara luas tetap menggunakan peradilan adat Aceh yang biasanya, meskipun sengketa itu terjadi dengan suku yang berbeda. Pernyataan tersebut dikuatkan oleh tokoh adat Tampur Paloh yang dianggap paling senior saat ini. Untuk penyelenggaraan perangkat peradilan adat ada Dua tahapan, yang pertama melalui lembaga adat gampong dan lembaga adat di tingkat permukiman. Mulai dari menerima laporan dan mengevaluasi konflik hingga tahap persidangan akhir dan mengeluarkan keputusan di pengadilan adat, penyelenggara adat bertanggung jawab atas semua tahapan pengadilan hukum adat. Putusan pengadilan adat juga harus memberikan rasa keadilan bagi kedua belah pihak, menurut pejabat pengadilan adat.